THE INFLUENCE OF FINANCIAL LITERACY, PARENTS'S INCOME, LIFESTYLE AND CAMPUS ENVIRONMENT ON STUDENTS' PERSONAL FINANCIAL MANAGEMENT BEHAVIOR - Nor Junita, Alif; Aslamiyah, Suaibatul (Universitas Muhammadiyah Tangerang, 2024)
This research aims to explore financial understanding, parental income, as well as living habits and campus environment on the financial behavior of management students at Muhammadiyah University of Gresik. Types of primary data quantitative methods. Research location at Muhammadiyah University Gresik, sample of 246 management students. The approach applied is multiple linear regression. Financial literacy makes a beneficial contribution, although not reaching a relevant level of significance, to the personal financial management behavior of financial management students at Muhammadiyah University of Gresik. Parental income shows a significant positive influence on the financial management behavior of management students at Muhammadiyah University of Gresik which is positively and significantly influenced by lifestyle. Likewise, the influence of the campus environment has a positive and significant impact on personal financial management behavior. management student at Muhammadiyah University of Gresik.